2010
DOI: 10.1089/act.2010.16407
|View full text |Cite
|
Sign up to set email alerts
|

Tension Headaches: Emerging Complementary Therapies

Abstract: This nutritional-based fermentate appeared to be safe and efficacious in a unique at-risk population and should receive more clinical research as a potential method to reduce the incidence of cold and flu-like symptoms, in individuals with and without a history of influenza vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Research in various animal species has demonstrated the effectiveness of SCFP to improve health and performance. In humans, supplementation of SCFP has been shown to improve immune responses to flu and allergy (Moyad et al, 2008(Moyad et al, , 2009(Moyad et al, , 2010 as well as modulate gut microbiota (Pinheiro et al, 2017). SCFP has been reported to increase ADG in growing piglets (Shen et al, 2009) and enhance reproductive performance in sows (Kim and Brandherm, 2008;Kim et al, 2010;Shen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research in various animal species has demonstrated the effectiveness of SCFP to improve health and performance. In humans, supplementation of SCFP has been shown to improve immune responses to flu and allergy (Moyad et al, 2008(Moyad et al, , 2009(Moyad et al, , 2010 as well as modulate gut microbiota (Pinheiro et al, 2017). SCFP has been reported to increase ADG in growing piglets (Shen et al, 2009) and enhance reproductive performance in sows (Kim and Brandherm, 2008;Kim et al, 2010;Shen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%